The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0271045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a fennel seed extract on the STAT signaling and intestinal barrier function

Abstract: Background Foeniculum vulgare, F. vulgare, commonly known as fennel, is believed to be one of the world’s oldest medicinal herbs and has been exploited by people for centuries as a nutritional aid for digestive disorders. In many southeast Asian countries, it is ingested as an after-meal snack, mukhvas, due to its breath-freshening and digestive aid properties. F. vulgare is used in some countries, such as Iran, as a complementary and alternative treatment for inflammatory bowel disease (IBD). Methods This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…The probiotic strains B. longum ES1 and L. acidophilus NCFM ® employed in this study were accompanied by bioactive ingredients. In contrast to findings reported by other authors who observed a beneficial modulation of intestinal microbiota through the use of, for instance, lavender extract, fennel, chamomile, or omega 3 fatty acids [22][23][24][25][26], our results indicate that in the two supplemented formulations, PI and GP, the additional components did not have a significant impact on the composition or metabolism of the intestinal microbiota. Lastly, the results support the pre-existing scientific evidence that the benefits increase if more than one probiotic, such as lactobacilli, is combined with bifidobacteria [65,66].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The probiotic strains B. longum ES1 and L. acidophilus NCFM ® employed in this study were accompanied by bioactive ingredients. In contrast to findings reported by other authors who observed a beneficial modulation of intestinal microbiota through the use of, for instance, lavender extract, fennel, chamomile, or omega 3 fatty acids [22][23][24][25][26], our results indicate that in the two supplemented formulations, PI and GP, the additional components did not have a significant impact on the composition or metabolism of the intestinal microbiota. Lastly, the results support the pre-existing scientific evidence that the benefits increase if more than one probiotic, such as lactobacilli, is combined with bifidobacteria [65,66].…”
Section: Discussioncontrasting
confidence: 99%
“…These components help relieve symptoms such as abdominal pain, bloating, irregular bowel movements, reflux, and heartburn. It is important to note that these ingredients not only influence intestinal cells by modulating inflammation, redox state, pain perception, and immune responses, but they also potentially affect the balance and activity of the intestinal microbiota [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The average PASI improvement was 34.21% versus 1.85% for the placebo. Vitamin D supplementation increased the results of psoriasis therapy (Das et al 2022 ). Aurochem Laboratories Pvt.…”
Section: Natural Sources Of Psoriasis Treatmentmentioning
confidence: 99%
“…Foeniculi fructus ( F. fructus ; Foeniculum vulgare or fennel) is an umbelliferous plant that is indigenous to southern Europe and the Mediterranean region. It has a long history of traditional herbal medicine use in both China and Europe, dating back to ancient times [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. This herb has been employed as a natural remedy for various digestive ailments, such as flatulence, bloating, and indigestion.…”
Section: Introductionmentioning
confidence: 99%
“…This herb has been employed as a natural remedy for various digestive ailments, such as flatulence, bloating, and indigestion. Additionally, it possesses antipyretic, analgesic, and antioxidant properties [ 5 , 6 , 7 ]. F. fructus provides relief from symptoms associated with female menopausal syndrome, helps regulate menstruation, and enhances libido [ 8 ].…”
Section: Introductionmentioning
confidence: 99%